2014
DOI: 10.3389/fnhum.2014.00963
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of gait changes in subjects with visual height intolerance when exposed to heights

Abstract: Introduction: Visual height intolerance (vHI) manifests as instability at heights with apprehension of losing balance or falling. We investigated contributions of visual feedback and attention on gait performance of subjects with vHI.Materials and Methods: Sixteen subjects with vHI walked over a gait mat (GAITRite®) on a 15-m-high balcony and at ground-level. Subjects walked at different speeds (slow, preferred, fast), during changes of the visual input (gaze straight/up/down; eyes open/closed), and while doin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
2
14
1
2
Order By: Relevance
“…This is consistent with studies that have shown patients with cerebellar ataxia to perform worse when walking at speeds slower than normal relative to faster, possibly due to greater sensory demands and/or greater demands placed on balance brought about through inertia [46]. Furthermore, the Lo template was designed to be more challenging than the Sh by using more extreme variations in step lengths.…”
Section: Discussionsupporting
confidence: 71%
“…This is consistent with studies that have shown patients with cerebellar ataxia to perform worse when walking at speeds slower than normal relative to faster, possibly due to greater sensory demands and/or greater demands placed on balance brought about through inertia [46]. Furthermore, the Lo template was designed to be more challenging than the Sh by using more extreme variations in step lengths.…”
Section: Discussionsupporting
confidence: 71%
“…In summary, based on both the current findings, which show a difference between the speed that minimizes the COT and the preferred speed on rough terrain, and previous research (Brown et al, 2002;Clark-Carter et al, 1986;Monsch et al, 2012;Schniepp et al, 2014), it seems that simply minimizing COT does not fully represent the human objective function for walking speed. Other walking conditions should be examined to investigate additional parameters that might appear in the cost function, such as stability, reward and time-saving (Summerside, et al, 2018).…”
Section: Discussioncontrasting
confidence: 49%
“…Monsch et al (2012) found that when instructed to walk downhill with a 'loose relaxed gait', subjects had a lower COT than when walking with their natural, preferred gait without any instructions. Similarly, it was found that people walk more slowly on a smooth surface when it is elevated above the ground (Brown et al, 2002;Schniepp et al, 2014) and thus presumably they chose not to walk at the energetic COT minimum. Kalantarov et al (2018) found that pedestrians crossing a street increased their walking speed when the time gap between cars was smaller.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Walking is slow and cautious [40,41]. Anxiety appears to be the critical symptom that causes the typical, but non-specific eye and motor behavior which can be described as tonic immobility [6].…”
Section: Visual Height Intolerance and The Course Of Anxiety Developmentmentioning
confidence: 99%